Pengaruh Demonstrasi Terhadap Kesadaran Energi Biogas Siswa SMPN 13 Balikpapan - Mardiana; Meira Putri Maharani; Inggrid Angelina Ansek; Hirzi Ashka Mazzaya; Arvel Zeva Fabian Dzulfikar; Arya Cakra Okta Nugraha; Algi Setiawan; A’am Putra Satria Harryrossa; Abdul Gafar Karim; Aprilino Alfa Kurmasela (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (KKN) activity focused on assessing the effectiveness of biogas technology socialization as a follow-up to the construction of low-cost biogas installations using plastic water tanks in Teritip Village, RT 14. The dissemination was carried out at SMP Negeri 13 Balikpapan through interactive counseling methods, which included showing a video demonstration of the installation's flame and conducting a quiz with prizes to increase student engagement. The KKN team also provided a guidebook as feedback to the school on the use of organic waste in the school environment. The activity was evaluated through a questionnaire filled out by 28 students. The results showed that 53.6% of students achieved the highest level of understanding (score 5) about how biogas works, and 82.1% expressed interest in learning more. These findings confirm that an educational approach combining visual demonstrations and active interaction is effective in improving energy literacy and encouraging student interest in renewable energy technology.  Translated with DeepL.com (free version).